Chemical constituents from the stems of Dendrobium gratiosissimum and their biological activities. (September 2022) - Li, Changkang; Sun, Xincheng; Song, Zhijun; Sun, Jiawei; Li, Yan; Wang, Nan; Zhang, Dan; Ye, Fei; Dai, Jungui
Abstract: Eight C6 –C3 -based bibenzyl derivatives (dengraphenols A–G, K), three mono -bibenzyls (dengraphenols I, L–M), one bis -bibenzyl (dengraphenol H), one oxyneolignane (dengraphenol J), one phenanthrene (dengraphenol N), and one picrotoxane-type sesquiterpene (dengrasusane A) were isolated from the stems of Dendrobium gratiosissimum . The resolution of dengraphenols A–J by chiral HPLC afforded ten pairs of enantiomers [(±)-dengraphenols A–J]. Their structures with absolute configurations were elucidated on the basis of comprehensive spectroscopic analyses, computational calculation methods and single-crystal X-ray diffraction, among which twenty-four [(±)-dengraphenols A–E, (+)-dengraphenol F, (±)-dengraphenols G–J, dengraphenols K–N, dengrasusane A] were undescribed. Ten compounds [(±)-dengraphenol B, (±)-dengraphenols D–E, (±)-dengraphenol H, (−)-dengraphenol I and dengraphenol N)] showed potent cytotoxicity against eight human cancer cell lines (A431, A2780, H460, HCT8, BGC823, SW1990, Daoy, and HGC27) with IC50 values of 3.77–9.75  μ M. At a concentration of 10  μ M, (−)-dengraphenol C, (±)-dengraphenol F, and (±)-dengraphenol K exhibited remarkable hepatoprotective activity against APAP-induced toxicity with a cell survival rate of 65.8%, 70.6% and 73.5%, respectively; dengraphenol N displayed significant anti-inflammatory effects; and dengraphenol K showed strong inhibitory activity against α -glucosidase with IC50 values of 5.71  μ M. These results would provide potential compounds for drug discovery. Graphical abstract: Bibenzyls, phenanthrenes and picrotoxane-type sesquiterpenoids were isolated from Dendrobium gratiosissimum Rchb. f. (Orchidaceae), among them, bibenzyls and phenanthrenes exhibited good cytotoxic, hepatoprotective, anti-inflammatory and hypoglycemic activities. Image 1 Highlights: Twenty-four undescribed compounds were isolated from the stems of Dendrobium gratiosissimum. All structures with absolute configurations were completely determined. These compounds exhibited cytotoxic, hepatoprotective, anti-inflammatory activities et al.